Roles of Nitric Oxide in the Regulation of Reproduction: A Review - Luo, Yuxin; Zhu, Yanbin; Basang, Wangdui; Wang, Xin; Li, Chunjin; Zhou, Xu (Frontiers in Endocrinology, 2021)
Nitric oxide (NO) has attracted significant attention as a stellar molecule. Presently, the study of NO has penetrated every field of life science and NO is widely distributed in various tissues and organs. This review demonstrates the importance of NO in both male and female reproductive processes in numerous ways, such as in neuromodulation, follicular and oocyte maturation, ovulation, corpus luteum degeneration, fertilization, implantation, pregnancy maintenance, labor and menstrual cycle regulation, spermatogenesis, sperm maturation, and reproduction. However, the mechanism of NO action remains unclarified, and the use of these mechanisms to treat some clinical fertility diseases will be of great significance.